2011
DOI: 10.1111/j.1476-5829.2011.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the management of localized mucocutaneous oral lymphoma in dogs: 14 cases

Abstract: Oral mucocutaneous lymphoma is rare in dogs. Surgery and chemotherapy do not usually provide effective long-term control. The objective of this study was to retrospectively evaluate survival of dogs with localized oral lymphoma treated with radiation therapy. The medical database of three institutions was searched for dogs with diagnosis of oral lymphoma treated with radiotherapy. Dogs with evidence of systemic disease were excluded. Survival was calculated with the Kaplan-Meier method and prognostic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…The gross and microscopic of representative sections of the neoplasm revealed a growth similar to other bovine lymphomas [2,6,13]. In the canine species, the prevalence of oral cavity lymphomas is greater, and includes the epitheliotropic type as the more common presentation [1,20]. However, in the tumor affecting the cow of this report, no neoplastic cells were visualized in the mucosal epithelial lining of the oral cavity justifying the classification of the tumor as non-epitheliotropic lymphoma.…”
Section: Discussionsupporting
confidence: 53%
“…The gross and microscopic of representative sections of the neoplasm revealed a growth similar to other bovine lymphomas [2,6,13]. In the canine species, the prevalence of oral cavity lymphomas is greater, and includes the epitheliotropic type as the more common presentation [1,20]. However, in the tumor affecting the cow of this report, no neoplastic cells were visualized in the mucosal epithelial lining of the oral cavity justifying the classification of the tumor as non-epitheliotropic lymphoma.…”
Section: Discussionsupporting
confidence: 53%
“…Radiotherapy can be used for local treatment or palliation for canine EL . In a retrospective case series of 14 dogs with mucocutaneous oral lymphomas (of which 12 had EL) treated with coarse fractionation radiotherapy, the ORR was 67% with a MST of 770 days .…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology for this malignancy in dogs is unknown . The tumour tends to occur in the epidermis, superficial dermis and periadnexally, although oral mucosal and mucocutaneous forms have been described . Canine EL is typically a tumour of T lymphocytes, with the CD3 + and CD4‐/CD8+ phenotype most commonly expressed .…”
Section: Introductionmentioning
confidence: 99%
“…Of these 14 dogs, 6 had T-cell epitheliotropic lymphoma. 10 Recent human studies have also shown promising results. 4,5 Masitinib is a tyrosine kinase inhibitor (TKI) targeting KIT receptor and platelet-derived growth factor receptor (PDGFR).…”
Section: Introductionmentioning
confidence: 99%
“…A case series with 14 dogs with mucocutaneous oral lymphomas treated with radiotherapy showed an overall response rate of 67%. Of these 14 dogs, 6 had T‐cell epitheliotropic lymphoma . Recent human studies have also shown promising results …”
Section: Introductionmentioning
confidence: 99%